Influencia de las relaciones de genero en el empoderamiento de las mujeres participantes del programa "emprende trujillo" de la municipalidad provincial de trujillo. trujillo 2014 - Blas Orbegoso, Natali Roxana (2015)
This research addresses gender inequality they face in their daily lives, women participating in the "Emprende Trujillo" program of the Provincial Municipality of Trujillo; based on gender relations still persist in our present, which lead to women are in a subordinate position relative to men and not have the same opportunities in terms of access and control of resources and services. Likewise, in the thesis discloses that despite the "Emprende Trujillo" program gives the 49 participating women, the opportunity to receive technical training, develop production units have a seed capital and a small business; gender relations and way of thinking about gender stereotypes, (attributes, roles and spaces), limits its influence and psychological empowerment, in relation to access and control capabilities development, social empowerment, based on access and control over productive resources and sources of wealth; and political empowerment, based on the access and control in decision-making by women to personal and family level.